In Situ Monitoring of Heterogeneous Hydrosilylation Reactions Using Infrared and Raman Spectroscopy: Normalization Using Phase-Specific Internal Standards. Issue 11 (November 2019) - Chen, Xiaoyun; Cheng, Yang; Matsuba, Masashi; Wang, Xianghuai; Han, Shuangbing; Jordan, Mowbray; Zhu, Qing
Heterogeneous reaction systems are prevalent in the chemical industry. In situ monitoring of heterogeneous reaction systems by vibrational spectroscopy techniques offers real-time composition and conversion information without sampling and with minimal perturbation. The multiphase nature introduces new challenges which are not typically encountered in the monitoring of homogeneous systems. We investigated the kinetics of the Pt catalyzed hydrosilylation reactions between allyl polyether and SiH containing silicone using both infrared (IR) and Raman spectroscopy. The reaction mixture remains biphasic for the majority of the reaction time due to the low miscibility of polyether and silicone. The results demonstrated that by normalization with appropriate internal standards (phase-specific normalization), more accurate quantitation of the SiH and allyl functional groups can be achieved based on in situ Raman results than that based on in situ attenuated total reflection Fourier transform infrared (ATR FT-IR) results. This is believed to be due to the wavelength-dependent penetration depth of the ATR mode. Raman results were obtained using two immersion optics with different focal lengths. The advantages and disadvantages of these two immersion optics are clearly illustrated in this study.